Respiratory and motor rehabilitation in the patients with chest drainage - Katarzyna Topczewska; Alicja Korwel; Anna Stangret; Aleksandra Goryniak-Mikołajczyk; Angelika Szczęśniak; Agata Mularczyk (Kazimierz Wielki University, 2019)
Introduction: Chest drainage is a procedure applied in life or health-threatening situations. It is an integral part accompanying patients undergoing thoracic surgery. It allows evacuation from the pleural cavity of pathological fluid, blood, air and perulence. The patients with chest drainage are struggling with many symptoms, such as pain, feeling of pressure or dyspnoea associated with a given disease entity through movement restrictions, especially on the side affected by drainage. Currently, respiratory and motor rehabilitation is an important part of treatment in patients undergoing thoracic surgery. Breathing and movement exercises and other elements of rehabilitation are of great importance in the whole treatment process, and when applied together, properly and regularly contribute to improvement of patient's health, reduce the risk of complications and improve the comfort of treated person. The goal of the thesis: The goal of the thesis was to review literature about pulmonary rehabilitation in patients with chest drainage. Results: Respiratory and motor rehabilitation conducted in the patients with chest drainage has a significant impact on their recovery. Educating patients about postoperative rehabilitation has a beneficial effect on their performance of individual rehabilitation elements.